Surgery in Perinatology - E. M. Halimun (Paediatrica Indonesiana, 1995)
Although modem neonatal surgery is a very young subject, it started only after the second world war, the progress is remarkable. The well intergrated interdisciplinary team among pediatric surgeons, pediatricians, neonatologits, anaesthetists, and other relevant specialists made this progress possible. Neonatal surgrey has been influenced by the advances in prenatal diagnosis. Neonatal surgical emergencies are related to perinatal conditions such as better antenatal care, including ultrasonogram examination, encourage the high risk pregnant women to deliver at pediatric/perinatal centers where obstetricians, pediatricians or neonatologist, pediatric surgeon, anesthetist are working as a team. Prenatal diagnosis has been one of the most challenging aspects in perinatology, and may directly related to the task of the pediatric surgeons to salvage certain type of malformations. Some experience of perinatal surgery is also discussed.